The Effect Of Coconut Drain Compost Fertilizer On The Growth And Production Of Tomato Plants (Solanum Lycopersicum L.) - yoni (PUCUK : Jurnal Ilmu Tanaman, 2025)
Tomatoes are a popular fruit and vegetable due to their delicious, fresh, and slightly sour taste. Besides being eaten raw, they can also be processed into various foods such as jam, sauce, and chili sauce. Demand for tomatoes continues to increase year by year. Cultivating tomatoes requires fertilizer. Farmers mostly use chemical fertilizers, potentially leading to land degradation due to excessive chemical use. Coconut pulp is a solid waste product from coconut milk and coconut oil processing. Coconut pulp is often discarded, but it can be used as compost because it contains nutrients that can help improve soil fertility. This study was conducted to determine the growth and production response of tomato plants with the application of coconut pulp compost. This study was conducted at the experimental garden of the Faculty of Agriculture, Pasir Pengaraian University, from December 2024 to March 2025. The method used was a Completely Randomized Design (CRD) with 4 treatments, each consisting of 3 replications, and each plot consisting of 6 plants, each containing 3 sample plants, resulting in a total population of 72 plants. The results showed that the addition of coconut pulp compost significantly affected all observed parameters, namely plant height, leaf number, flowering time, and fruit weight. The best dose obtained was 150 grams per polybag of coconut pulp compost in treatment (P2).